A Review of Aging and the Lower Urinary Tract: The Future of Urology - Nishii, Hisae (International neurourology journal, 2021)
Lower urinary tract symptoms (LUTS) are common among elderly people, with significant effects on individuals, caregivers, and the wider health care system. As the elderly population with multiple comorbidities is increasing, the burden of LUTS will increase. This review describes the demographic trends in the aging society, changes in lower urinary tract function with aging, and deterioration of physical and cognitive function in aging, as well as what has been done regarding geriatric urology and what urologists should do to meet the health care needs of the aging population. Frailty and dementia are unmissable factors in the evaluation of elderly patients. Numerous reports have described associations between LUTS and frailty and between LUTS and dementia. Urologists must be aware of the multiplex physical, cognitive, and social characteristics of elderly people. Maintaining a geriatric viewpoint in the diagnosis, treatment, and management of elderly individuals with LUTS will fulfill the unmet needs of elderly people. It is also essential to discuss the treatment and management goals of LUTS with patients and caregivers. Active case identification, appropriate evaluations of LUTS and comorbidities, and a multidisciplinary approach with other health-care professionals are recommended for better treatment and management.